Dental healthcare utilisation among young adults who were in societal out‐of‐home care as children: A Swedish National Cohort Study. (23rd July 2018) - Berlin, Marie; Mensah, Tita; Lundgren, Frida; Klingberg, Gunilla; Hjern, Anders; Vinnerljung, Bo; Cederlund, Andreas
Abstract : We used Swedish national registers to analyse dental health care among young adults with childhood experience of out‐of‐home care (OHC), in Cox regression analyses. All 1.7 million Swedish residents born in 1980–1994 were included, of whom 4% had been in OHC. The population was followed up in the Dental Health Register from age 20 to 29, during the period 2009–2014. We found that persons with short or long OHC experience made emergency dental care visits more often than their majority‐population peers: 17–23% versus 9–10%, (adjusted Hazard ratios [HR:s] 1.60–2.02); they more often had tooth extractions, 9–12% versus 3% (HR:s 2.33–3.03); but less regularly visited a dentist for planned check‐ups, 61–77% versus 80–87% (HR:s 0.76–0.78). Since dental health in young adulthood reflects dental health and dental care in childhood, the findings of this study call for improved preventive dental health care for children in OHC.